2018
DOI: 10.1002/cncr.31726
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of radical prostatectomy with adjuvant radiotherapy versus radiotherapy plus androgen deprivation therapy for men with advanced prostate cancer

Abstract: BACKGROUND: Men with locally (LAPCa) or regionally advanced (RAPCa) prostate cancer are at high risk of death from their disease. Clinical guidelines support multi-modal approaches, which include radical prostatectomy (RP) followed by radiotherapy (XRT) or radiotherapy plus androgen deprivation therapy (ADT). However, limited data exists comparing these substantially different treatment approaches. Using SEER-Medicare data, we compare survival outcomes and adverse effects associated with RP+XRT vs XRT+ADT in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 44 publications
3
35
1
Order By: Relevance
“…We observed that men with locally advanced prostate cancer and/or node‐positive disease treated with radical prostatectomy and adjuvant radiotherapy had a lower risk of death from prostate cancer and improved overall survival in comparison with men treated with radiotherapy plus ADT . Our findings are analogous to data published in studies of men with localized prostate cancer, which have shown that surgery, compared with radiation, may have a greater impact in those with higher risk disease .…”
supporting
confidence: 86%
See 1 more Smart Citation
“…We observed that men with locally advanced prostate cancer and/or node‐positive disease treated with radical prostatectomy and adjuvant radiotherapy had a lower risk of death from prostate cancer and improved overall survival in comparison with men treated with radiotherapy plus ADT . Our findings are analogous to data published in studies of men with localized prostate cancer, which have shown that surgery, compared with radiation, may have a greater impact in those with higher risk disease .…”
supporting
confidence: 86%
“…We agree that there are inherent limitations in the use of observational data for comparing 2 different treatment approaches. These limitations are detailed clearly in our publication’s Discussion section …”
mentioning
confidence: 97%
“…Currently, both surgery and radiation therapy were recommended as a first-line treatment option for LAPC patients [41]. There were always several controversies in treatment tactics with the consideration of patient survival and the quality of life [52][53][54][55]. But there was no doubt that surgery could provide accurate pathological stage for patients.…”
Section: Clinical Significance Of Cystoprostatectomy In Lapcmentioning
confidence: 99%
“…These limitations are detailed clearly in our publication's Discussion section. 1 The ideal treatment for men with high-risk prostate cancer is a subject of wide debate. Ideally, evidence to guide care is generated in the setting of prospective…”
Section: Reply To Effectiveness Of Radical Prostatectomy With Adjuvanmentioning
confidence: 99%
“…In a newly published retrospective study, Jang et al had compared the survival outcomes and associated adverse effects for a large cohort of patients affected by local or regional advanced prostate cancer who underwent radical prostatectomy followed by radiotherapy (XRT) or XRT plus androgen deprivation therapy (ADT) from 1992 to 2009, and they had showed a significantly lower risk of prostate cancer–specific death and improved overall survival in the first group of patients in comparison with those men treated with XRT plus ADT.…”
mentioning
confidence: 99%